Democracy challenged: how parties politicize different democratic principles - Engler, S; Gessler, T; Abou-Chadi, T; Leemann, L (Routledge, 2022)
Scholars have paid increasing attention to how questions of multi-level governance have become politicized in the domestic political arena. Issues surrounding democratic government itself have received surprisingly little attention in this debate. In this article, we ask how political parties politicize the principles of liberal democracy within advanced democracies. We expect that challenger parties are most likely to question existing principles. The targets of their criticism, however, should vary according to their ideological origins. Conducting automated quantitative text analysis of Swiss, German and Austrian party press releases between 2006 and 2018 using a multidimensional dictionary of liberal democracy, we confirm that left-libertarian and populist radical right parties are the main challengers of the democratic status quo. The foundation of criticism, however, differs fundamentally. While left-libertarians focus on principles that strengthen individual autonomy in politics, populist radical right parties demand more forms of participation and fewer constraints by liberal elements of democracy.